Sundhed, glæde, fællesskab - og hvor modsætningerne ligger. Om idrættens enhed og mangfoldighed i Finland - Eichberg, Henning (Forum for Idræt, 2000)
Diskussion af historieskrivning med bl.a. Helsingfors Gymnastikklubb og olympismens historiske faser fra slutningen af 1800-tallet og frem som eksempler. Health, pleasure, brotherhood – and where are the contradictions? On unity and diversity in Finnish sports Some recent publications of Finnish research tell important stories about the otherness and heterogenity of sport in Finnish history. But they also do more than this. Some fundamental questions are being raised about the nature of history, about tradition, change and disappearance. How does research understand its own relation to the organised “unity” of Olympic sport – and to the diversity of conflicting body cultures? And how do researchers find their place or move between an integration into the “monotheism of achievement”, an individual subjectivity and the solidarity of cultural struggle?